Searching for ejected supernova companions in the era of precise proper motion and radial velocity measurements. Issue 2 (8th April 2023) - Chrimes, A A; Levan, A J; Eldridge, J J; Fraser, M; Gaspari, N; Groot, P J; Lyman, J D; Nelemans, G; Stanway, E R; Wiersema, K
ABSTRACT: The majority of massive stars are born in binaries, and most unbind upon the first supernova. With precise proper motion surveys such as Gaia, it is possible to trace back the motion of stars in the vicinity of young remnants to search for ejected companions. Establishing the fraction of remnants with an ejected companion, and the photometric and kinematic properties of these stars, offers unique insight into supernova progenitor systems. In this paper, we employ binary population synthesis to produce kinematic and photometric predictions for ejected secondary stars. We demonstrate that the unbound neutron star velocity distribution from supernovae in binaries closely traces the input kicks. Therefore, the observed distribution of neutron star velocities should be representative of their natal kicks. We evaluate the probability for any given filter, magnitude limit, minimum measurable proper motion (as a function of magnitude), temporal baseline, distance, and extinction that an unbound companion can be associated with a remnant. We compare our predictions with results from previous companion searches, and demonstrate that the current sample of stars ejected by the supernova of their companion can be increased by a factor of ∼5–10 with Gaia data release 3. Further progress in this area is achievable by leveraging the absolute astrometric precision of Gaia, and by obtaining multiple epochs of deep, high resolution near-infrared imaging with the Hubble Space Telescope,   JWST and next-generation wide-field near-infrared observatories such as Euclid or the Nancy Grace Roman Space Telescope .